A Silole‐Based Efficient Electroluminescent Material with Good Electron‐Transporting Potential. Issue 8 (12th June 2015) - Quan, Changyun; Nie, Han; Hu, Rongrong; Qin, Anjun; Zhao, Zujin; Tang, Ben Zhong
Abstract A new silole derivative, 2, 5‐bis(7‐(dimesitylboranyl)‐9, 9‐dimethylfluoren‐2‐yl)‐1‐methyl‐1, 3, 4‐triphenylsilole ((MesBF)2MTPS), is synthesized and characterized. (MesBF)2MTPS shows a good fluorescence efficiency of 15% in THF solution and a higher efficiency of 86% in solid film, presenting an aggregation‐enhanced emission characteristic. It is thermally and morphologically stable, with high decomposition and glass‐transition temperatures of 257 and 171°C, respectively. The LUMO energy level (−2.96 eV) of (MesBF)2MTPS is lower than that of TPBi, revealing its electron‐transporting potential. Efficient organic light‐emitting diodes (OLEDs) are fabricated using (MesBF)2MTPS as emitter, which radiates yellow light at 554 nm, and affords high maximum luminance, current efficiency, and external quantum efficiency of 48348 cd·m−2, 12.3 cd·A−1, and 4.1%, respectively.